Praktik Pendampingan Hukum Permohonan pada Posbakum yang Bekerjasama dengan Lembaga Bantuan Hukum Legundi - Dewi Rosita; Nadaa Avria Hanum (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
Legal assistance for applications is a crucial form of legal aid provided to the public in submitting various types of applications to the courts or related agencies. This research is motivated by the urgent need to understand the effectiveness and implementation of such legal aid services, particularly for underprivileged communities who face barriers in accessing the justice system. This article aims to discuss and describe in detail the application processing process carried out by the Legal Aid Post (Posbakum) when operating and collaborating with the Legundi Legal Aid Institute (LBH Legundi), specifically in the context of name change applications. This research uses normative legal methods with a conceptual and statutory approach to analyze the applicable procedures. The results show that Posbakum plays a central role in drafting name applications for communities in need through a phased assistance process that includes initial consultation, verification of document requirements, technical assistance in scanning and nazegel, drafting application letters, and guidance on case registration. This assistance model has proven effective in overcoming procedural obstacles and increasing access to justice for underprivileged communities, while simultaneously transforming the community from a passive to an active role in fighting for their civil rights.